Evaluating the implementation of curriculum in teaching reading and writing in Sepedi home language in Mankweng Circuit of Limpopo Province - Modiba, Phutiane Abram (My University, 2018)
The aim of this study is to evaluate the implementation of curriculum in the teaching of reading and writing in the Sepedi Home Language in the Mankweng Circuit of Limpopo Province. This result from the fact that intermediate learners are struggling to read and write in the Sepedi Home Language, and as a result are incompetent when reading and writing even in their language of teaching and learning, namely English. This signifies that mastering to read and write in the Sepedi Home Language, is likely to enable learners to read and write better in English as a language of teaching and learning. Of a huge surprise, the struggle to read and write in Sepedi Home Language occurs with every cohort of learners registered in the Intermediate Phase. For this reason, the study is designed to evaluate the manner in which Sepedi curriculum is being implemented in schools to address and respond to challenges of inability to read and write by intermediate Sepedi learners. This is a case study covering three primary schools and it is located within the qualitative research approach and phenomenology. The collection of data was done through individual face-to-face interviews, document study and diagnostic assessments. Each of the three schools forwarded three categories of research participants, namely, an HOD, a teacher and a parent whose child was doing Sepedi in the Intermediate Phase. Findings revealed that overcoming reading and writing inability by the intermediate learners needs to be a joint stakeholders’ effort. In addition, inadequate Sepedi materials and resources for intermediate learners need to be the apex priority by the Department of Basic Education. In view of the shared research results, the study recommends that there be well-coordinated participation of all stakeholders in the development of skills associated with reading and writing for the Sepedi Home Language Intermediate learners. Lastly, the study recommends that intermediate Sepedi learners be offered an opportunity to participate in Sepedi essay writing competitions wherein they are first given pamphlets and posters in Sepedi as a clue. Finally, the Sepedi Home Language needs to be equally protected and promoted just like it is the case with English from the Intermediate Phase upwards.
Thesis (M.Ed. (Language education)) -- University of Limpopo, 2018
Keywords: Curriculum implementation; Teaching, reading and writing; Sepedi; Curriculum planning; Curriculum change - South Africa - Limpopo